Qualidade de vida e saúde bucal autopercebida em idosos durante a pandemia por covid-19 - Mendonça, Priscilla Rolim (2022)
The aim of this study was to analyze factors related to the quality of life and self-perceived oral health of the elderly during the COVID-19 pandemic. This is a descriptive cross-sectional study with a quantitative approach, developed with 101 elderly people registered in the area covered by the UBS José Gomes da Silva Zumbi, located in Horizonte, Ceará, from June to August 2022. The Mini Mental State Exam was applied (MMSE) for cognitive screening of the elderly, as an inclusion criterion. For data collection, a structured interview form containing sociodemographic, general and oral health data, the WHOQOL-Bref instrument to assess quality of life and the GOHAI to know the self-perceived oral health of the elderly were used. Descriptive statistics were used for analysis, through absolute and relative frequencies, mean (c), and standard deviation (S), and inferential statistics, through ANOVA tests, Student's t test and Welch's t test, to investigate associations between the descriptive variables and the questionnaires applied in the study. The sample revealed a mean age of 68.1 years, female predominance (57.4%), 3 years of study, total edentulous (65.35%), no access to dental consultation during the pandemic (62.4%). The GOHAI index (31.5) obtained from the sample characterizes a moderate self-perception of oral health. The WHOQOL-Bref results, the assessment of quality of life (3.71), satisfaction with health (3.54) and scores for the physical (3.14), psychological (3.94) and environment domains environment (3.87) were regular. Only the social relationships domain (4.03) was evaluated as good. There was a significant association between GOHAI scores and the presence of dental problems (p=0.001), current oral condition equal to or worse than before the pandemic (p=0.007) and self-perception of good or poor oral health (p=0.006). A significant negative correlation was also observed between the WHOQOL-Bref domains and the variables “xerostomia” (p=0.01) and “diabetes mellitus” (p=0.006). No statistically significant differences were found between COVID-19 and GOHAI scores and WHOQOL-Bref domains. It is suggested the implementation of health education programs for the elderly with actions and strategies aimed at improving oral health and quality of life, in order to enable a better perception of their status and greater inclusion of this age group in the health care system. health.